EspC forms a filamentous structure in the cell envelope of Mycobacterium tuberculosis and impacts ESX‐1 secretion. Issue 1 (25th November 2016) - Lou, Ye; Rybniker, Jan; Sala, Claudia; Cole, Stewart T.
Summary: Pathogenicity of Mycobacterium tuberculosis ( M. tb ) is mediated by the ESX‐1 secretion system, which exports EsxA and EsxB, the major virulence factors that are co‐secreted with EspA and EspC. Functional information about ESX‐1 components is scarce. Here, it was shown that EspC associates with EspA in the cytoplasm and membrane, then polymerizes during secretion from M. tb . EspC was localized by immuno‐gold electron microscopy in whole cells or cryosections as a surface‐exposed filamentous structure that seems to span the cell envelope. Consistent with these findings, purified EspC homodimerizes via disulphide bond formation, multimerizes and self‐assembles into long filaments in vitro . The C‐terminal domain is required for multimerization as truncation and selected point mutations therein impact EspC filament formation, thus reducing secretion of EsxA and causing attenuation of M. tb . The data are consistent with EspC serving either as a modulator of ESX‐1 function or as a component of the secretion apparatus. Abstract : EspC is a small, helical hairpin protein restricted to pathogenic mycobacteria, like Mycobacterium tuberculosis, where it impacts the function of the ESX‐1 secretion system and controls pathogenesis. Purified EspC polymerizes into filaments with a diameter of 10–15 nm and similar structures may be found in the capsule layer. It is conceivable that the EspC filaments are either a component of the secretion apparatus itself or that they modulate its function in an essential manner.